2021
DOI: 10.3389/fpubh.2021.648424
|View full text |Cite
|
Sign up to set email alerts
|

How Cooperative Engagement Programs Strengthen Sequencing Capabilities for Biosurveillance and Outbreak Response

Abstract: The threat of emerging and re-emerging infectious diseases continues to be a challenge to public and global health security. Cooperative biological engagement programs act to build partnerships and collaborations between scientists and health professionals to strengthen capabilities in biosurveillance. Biosurveillance is the systematic process of detecting, reporting, and responding to especially dangerous pathogens and pathogens of pandemic potential before they become outbreaks, epidemics, and pandemics. One… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Intense efforts have been put over the last decade to introduce next generation sequencing and other tools in developing countries to improve biosecurity, biosafety, and biosurveillance to mitigate diseases ( 142 ). By increasing the capacity to test and do biosurveillance on more pathogens, we can get a more complete picture of the infectious disease risk in an area.…”
Section: Designing An Effective Surveillance Strategy At Abattoirsmentioning
confidence: 99%
“…Intense efforts have been put over the last decade to introduce next generation sequencing and other tools in developing countries to improve biosecurity, biosafety, and biosurveillance to mitigate diseases ( 142 ). By increasing the capacity to test and do biosurveillance on more pathogens, we can get a more complete picture of the infectious disease risk in an area.…”
Section: Designing An Effective Surveillance Strategy At Abattoirsmentioning
confidence: 99%
“…The virus had mutated over a period into different variants which confer increase in severity of infection, rapid transmission and immune escape which is of more concern (Harvey et al, 2021). Bio surveillance involves the early detection of pathogens and variants for mitigation efforts and limit its spread through continuous genome sequencing approaches (Bartlow et al, 2021). The genomic surveillance revealed that there are multiple lineages circulating in India and in other countries (Sarkar et al, 2021).…”
Section: Introductionmentioning
confidence: 99%